The implementation of vocational skills in teaching and learning of people with disabilities in the Community-Based Rehabilitation Center CBRC: a review from ecological environments perspective - Jamaluddin, Rahimah; Mat Sapak, Mur Fatehah; Abdul Kadir, Suhaida; Mohd Hajaraih, Syahidatul Khafizah; Kamis, Arasinah (Horizon Research Publishing, 2021)
Vocational education for students with learning difficulties (SLD) emphasizes theoretical teachings and practical experiences among students, while teaching them the knowledge and skills required for an occupation. Studies on the teaching of vocational skills for SLD focus mainly on students in the mainstream educational system. The current study aims to explore the teaching and learning of vocational skills for SLD in a Community-Based Rehabilitation Center (CBRC), in Selangor, Malaysia from an ecological environment's perspective. Six teachers from the CBRC were interviewed and observed. Results show teachers focused mainly on microsystem and mesosytem environments through the various strategies to support TnL of vocational skills' education for SLD. Insufficient pedagogical skills and vocational training among teachers, and inadequate physical facilities and equipment compromised the execution of TnL in this context. We suggest CBRC teachers incorporate exsosystem and macrosystem environments in TnL of vocational skills among children with learning disabilities through a community-based or project-based approach involving corporate social responsibility (CSR) to improve vocational skills in both students and teachers. Implications to the current practice are also discussed.